Analisis Rasio Likuiditas, Solvabilitas, dan Profitabilitas PT. Garuda Indonesia Persero Tbk Sebelum dan Setelah Penerapan PSAK 73 - Prasetyani, Filipe Sekar; Nugraeni (Dinasti Research, 2024)
Leasing is an agreement between the lessor (leasing company) and the lessee (customer) in which the lessor provides goods with the right to use by the lessee in exchange for rental payments for a certain period. PSAK 73, which was established in 2020, regulates the recognition, measurement, presentation and spread of rent, especially for lessee. PSAK 73 only allows lessees to classify leases as finance leases so that assets and liabilities from lease transactions are recognized in the statement of financial position, with offers for short-term leases and leases with low-based assets. The aim of this research is to find out how the implementation of PSAK 73 regarding rent has an impact on the financial performance of PT Garuda Indonesia (Persero) Tbk. This research uses financial ratio analysis Current Ratio, Debt to Asset Ratio, Debt to Equity Ratio, and Return On Asset Ratio